BUILDING STRATEGIC ADOPTION IN EVOLVING DIGITAL ECOSYSTEM FOR MSMEs - Indrayanti; Afandi, Ardian Rahman; Timur, Muhammad Idham Ananta; Triyaswati, Hilda; Sutrisno, Wahyu (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
With over 66 million Micro, Small, and Medium Enterprises (MSMEs), Indonesia relies heavily on this sector, which contributes 61% to the national GDP. However, many MSMEs—especially in regions like Bantul and Yogyakarta—face significant barriers to adopting digital technologies. This study examines how digital literacy training combined with SMART (Specific, Measurable, Achievable, Relevant, Time-bound) strategic planning influences MSME self-efficacy and digital skills. A mixed-method quasi-experimental design involving ten participants from five MSMEs was employed. Quantitative results indicated modest improvements in self-efficacy (2.74%) and digital skills (2.33%), though these were not statistically significant. However, qualitative data revealed enhanced digital confidence, increased awareness of online market potential, and persistent challenges related to strategy execution and technological access.